Comparison between nonperiodized resistance training and nonlinear periodization on muscular peak power in Brazilian soccer players - Legey, Sandro; Barsanulfo, Sílvio Roberto; Lamego, Murilo; Pinheiro, Braulio; Inacio, Pedro Augusto; Machado, Sérgio; Sá Filho, Alberto (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: For decades the literature has been investigating the ideal dose-response regarding the frequency, intensity and volume of training that optimize the increase in muscle strength and power in athletes and non-athletes. Objective: Evaluate the effects of strength training from a nonlinear (NLP) and non-periodized (NP) model on muscular peak power in soccer players. Methods: Twelve male junior football players from a professional team in Cabo Frio (Brazil) were recruited and randomly divided into two groups (6 in each group). The groups were randomly divided into: G1 - (Body mass: 64.7 ± 6.5 kg; Height: 172.3 ± 5.8 cm; % fat: 5.1 ± 2.7; Age: 17.5 ± 1.0 years) performed RT with NLP model; G2 - (Body mass: 66.1 ± 4.7; Height: 177.1 ± 6.1 cm; % fat: 5.1 ± 1.2, age: 17.6 ± 0.5 years) performed RT with NP model. Both groups are subjected to 12 weeks of training. PNL strength training consisted of weight training sessions on alternate days, 3 times a week, the rest intervals were 120s among the exercises and included 10 exercises. NLP distribution was as follows: Day 1 (3x4-6 maximum repetitions [RM] with rest intervals of 120 sec between sets); Day 2 (3x8-10RM with 60-90 rest intervals between sets); and day 3 (3x12-15RM with rest intervals of 60 sec between sets). NP training performed the same duration, weekly frequency, exercises and number of sets (3 sets 8-10RM and 60-90 sec rest intervals). Before and after NP and NLP training, muscle peak, speed and agility were evaluated. Results: The ANOVA with mixed model showed no significant interaction between group and moment (F(1,10) = 0.133; p=0.72), and no significant main effect for group (F(1,10) = 0.032; p=0.86) in muscular peak power. There was a significant main effect for moment (F(1,10) = 14.872; p=0.003), where were showed that Post-training presented higher values of muscular peak power compared to Baseline (p= 0.003). Conclusion: It is concluded that both training organization models are effective and can be used to develop peak muscle power.